Interest and Awareness as Factors Mediating the Content of Online Search Queries Made by Schoolchildren When They Are Doing Simple and Problem-Oriented Training Assignments - Svetlana A. Bezgodova; Anastasia V. Miklyaeva (Peoples' Friendship University of Russia (RUDN University), 2022)
Online search for additional information is an essential element of the educational activities of modern schoolchildren. However, the factors determining its effectiveness remain understudied. The article presents the results of a study of the contribution of awareness in the subject field of online search and interest in the subject of a training assignment to the content characteristics of online search queries made by schoolchildren when they are doing simple and problem-oriented training assignments. The study involved 206 schoolchildren studying in grades 5-9 of secondary schools, including 115 girls and 91 boys. The average age of the study participants was 13.24 ±1.56 years. The study was conducted using the experimental method and the questionnaire method. The study participants were asked to sequentially find information on the Internet and do first a simple training assignment, then a problem-oriented one, and assess their interest and awareness in the subject field of the search query. Mathematical processing was carried out using the Fischer φ* criterion and Mann - Whitney U test, ANOVA, and regression analysis. As a result, it was revealed that interest in the topic of the search query is not related to its qualitative and quantitative characteristics. The schoolchildren's awareness is related to the qualitative characteristics of clarifying search queries rather than to their number. It was found that simple training assignments are more conducive to searching the Internet for ready-made solutions for their implementation. Problem-oriented training assignments are more effective for stimulating schoolchildren's independent information search on the Internet than simple training assignments. The results of the study can be used for developing educational materials in the general educational practice.